Peran Model Pendidikan Wustho Terhadap Prestasi Belajar Siswa pada SMP PGRI 1 Ciambar Kec. Ciambar Kab. Sukabumi - Amir Mirdad; Siti Qomariyah; Nawil Hadad; Moh. Jujun Sirojudin (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
Wusto education is an Islamic values-based learning approach that aims to shape student character while improving academic achievement. This study was conducted to analyze the effect of the implementation of wusto education on student learning achievement at PGRI 1 Ciambar Junior High School, Ciambar District, Sukabumi Regency. This study used descriptive quantitative methods involving 100 students as samples. Data were collected through questionnaires, learning achievement tests, and interviews with teachers to better understand the implementation of wusto education in the school curriculum. The results showed that wusto education contributed positively to students' learning achievement. After the implementation of the wusto education program, there was an 18% increase in students' average academic score. In addition, the implementation of wusto education is able to shape better student characters, such as discipline, responsibility and honesty. The excellent programs of wusto education, such as halaqah, character-based learning and religious activities, have a significant impact on strengthening students' moral values. The integration of wusto education at SMP PGRI 1 Ciambar is done by incorporating religious values into general subjects and extracurricular activities. Teachers play an active role in managing learning that is balanced between academics and character building. Based on the results of the study, it is concluded that wusto education is significantly able to improve student learning achievement while forming superior character. The recommendation of this study is to expand the implementation of wusto education in other schools as a strategy to improve the quality of education.